2019
DOI: 10.1128/aac.00279-19
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolones in Drug-Resistant Tuberculosis: Culture Conversion and Pharmacokinetic/Pharmacodynamic Target Attainment To Guide Dose Selection

Abstract: Fluoroquinolones are group A drugs in tuberculosis guidelines. We aim to compare the culture conversion between new-generation (levofloxacin and moxifloxacin) and old-generation (ciprofloxacin and ofloxacin) fluoroquinolones, develop pharmacokinetic models, and calculate target attainment for levofloxacin and moxifloxacin. We included three U.S. tuberculosis centers. Patients admitted between 1984 and 2015, infected with drug-resistant tuberculosis, and who had received fluoroquinolones for ≥28 days were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…This result is similar to a PK/PD report of levofloxacin in acutely hospitalized elderly patients (27). A previous study demonstrated that a PK/PD model predicted that 500 mg levofloxacin was not effective for treating multidrug-and drug-resistant tuberculosis (47)(48)(49). By contrast, the fAUC 0-24 /MIC of levofloxacin reached 60 in lung tissue against S. pneumoniae.…”
Section: Discussionsupporting
confidence: 87%
“…This result is similar to a PK/PD report of levofloxacin in acutely hospitalized elderly patients (27). A previous study demonstrated that a PK/PD model predicted that 500 mg levofloxacin was not effective for treating multidrug-and drug-resistant tuberculosis (47)(48)(49). By contrast, the fAUC 0-24 /MIC of levofloxacin reached 60 in lung tissue against S. pneumoniae.…”
Section: Discussionsupporting
confidence: 87%
“…However, comparative data are available from a MDR-TB trial (no difference in treatment outcomes when comparing the two drugs; fewer adverse events for M) [23], and rabbit and mouse models (M broadly superior over Lfx) [24,25]. Lfx doses in such studies may have been too low [26,27]. Further RCTs are required.…”
Section: Discussionmentioning
confidence: 99%
“…Noncompartmental analysis was performed to estimate the area under the concentration-time curve over 24 h (AUC 0-24 ) using serum concentrations in Phoenix WinNonlin version 8.0 (Certara USA, Princeton, New Jersey). Based on previous studies of PK/PD and treatment outcomes, [ 6 , 7 ] serum levofloxacin C max of 8 μg/mL and AUC 0-24 of 80 μg × h/mL were used as the standard-of-care targets during anti-TB treatment, [ 15 ] as concentrations below these breakpoints have previously predicted poor long-term treatment outcome. To determine the best time interval for the collection of urine samples, serum AUC 0-24 was compared with urine concentrations at 0–4 h, 4–8 h, and 8–24 h using linear correlation.…”
Section: Methodsmentioning
confidence: 99%
“…[ 5 ] Among people treated for MDR-TB, it has been demonstrated that serum levofloxacin AUC/MIC ratios below certain population targets associate with treatment failure and were in fact the most important predictor of treatment outcome in adjusted analyses. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%